2021
DOI: 10.5334/pb.1093
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness May Buffer Psychological Distress in Adolescents during the COVID-19 Pandemic: The Differential Role of Mindfulness Facets

Abstract: The COVID-19 pandemic strongly impacts adolescents' mental health, a population particularly vulnerable to mental disorders, highlighting the need to identify protective factors against COVID-19 related psychological distress to inform policies and intervention strategies. Previous research suggests that mindfulness may be a promising factor that can lower the risk of detrimental psychological consequences related to the COVID-19 pandemic. However, it is currently unknown which aspects of mindfulness contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 38 publications
4
9
0
Order By: Relevance
“…Overall, about 11.1% of the participants of our study reported feeling anxiety, 25.2% having depressive symptoms, and 10.9% experiencing suicidal ideation. Our findings align with prior research demonstrating poor mental health during disease outbreaks, as well as with studies that reported high levels of psychological distress in other samples during the COVID-19 pandemic (30,31) From the total, 70.4% reported experiencing economic hardship. Moreover, over 30% of our sample reported going through moderate and severe economic hardship.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, about 11.1% of the participants of our study reported feeling anxiety, 25.2% having depressive symptoms, and 10.9% experiencing suicidal ideation. Our findings align with prior research demonstrating poor mental health during disease outbreaks, as well as with studies that reported high levels of psychological distress in other samples during the COVID-19 pandemic (30,31) From the total, 70.4% reported experiencing economic hardship. Moreover, over 30% of our sample reported going through moderate and severe economic hardship.…”
Section: Discussionsupporting
confidence: 91%
“…Although the protective role of mindfulness on adolescent psychological distress has been found in previous studies (Klingbeil et al, 2017;Kock et al, 2021;Reangsing et al, 2021;Tan & Martin, 2015;Zhang et al, 2022), the current research is inconclusive as to whether mindfulness is always effective in reducing psychological distress (Johnson et al, 2017;Montero-Marin et al, 2022;Sibinga et al, 2016). Only one study has examined the effects of mindfulness in the context of COVID-19 and highlighted its significant buffering role against the risk posed by COVID-19 on psychological distress (Kock et al, 2021;Yeun & Kim, 2022). Moreover, previous research has three notable limitations.…”
Section: Introductionmentioning
confidence: 76%
“…Empirical studies on the consequences of COVID-19 on individuals' mental health have been booming recently (Chawla et al, 2021;Lantos et al, 2022; Simonovic et al, 2021), studies exploring adolescents' psychological consequences in double disasters are scarce (Simonovic et al, 2021). Moreover, the protective factor of mindfulness to reduce risks of psychological distress is promising in numerous studies (Kock et al, 2021;Reangsing et al, 2021;Zhang et al, 2022). While it is still unclear under what conditions or for whom mindfulness may not work, the development of prevention programs targeting COVID-19 and other disasters is critical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifth, this study did not directly measure baseline levels of psychological distress in pre-disaster adolescents, which made it difficult to fully demonstrate that the model in our study reflects a specific pattern for a double disaster. Future studies should compare baseline levels of psychological distress before and after a disaster to answer this question (Kock et al, 2021).…”
Section: Strengths Limitations and Future Directionsmentioning
confidence: 99%